PENINGKATAN HASIL BELAJAR PKN MATERI PEMILU DAN PILKADA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION - Jami'atus Solikah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2021)
The purpose of this study is to improve teacher performance, student learning activities, and student learning outcomes in electoral and election material by applying the STAD type cooperative learning model. This research is a classroom action research conducted in two cycles. Each cycle consists of two meetings and through four stages, namely planning, implementing actions, observing, and reflecting. The subjects in this study were the sixth grade students of Karngbinangun State Elementary School, Lamongan District, 2017/2018 school year, with 15 students consisting of 11 male students and 4 female students. Data collection techniques used are test and non-test techniques. Data analysis was carried out by analyzing qualitative and quantitative data. Based on the implementation of the first cycle the value of teacher performance is 83.08 (AB). In the second cycle, the teacher's performance score increased to 89.17 (A). Student learning activities reached 65.12% and in the second cycle increased to 79.87%. In the first cycle, the average value of student learning outcomes reached 70.67 with a complete percentage of classical learning of 66.67%. Meanwhile, in the second cycle the average value of student learning outcomes increased to 81.67 with a complete percentage of classical learning at 93.33%.